Exchange-Rate Arrangements an Financial Integration in East Asia: On a Collision Course? - Hans Genberg (Oesterreichische Nationalbank (OeNB), 2006)
Financial integration in Ease Asia is actively being pursued and will in due course lead to substantial mobility of capital between economies in the region. Plans for monetary cooperation as a prelude to monetary integration and ultimately monetary unification are also proposed. These plans often suggest that central banks should adopt some form of common exchange rate policy in the transition period towards full monetary union. This paper argues that this is a dangerous path in the context of highly integrated financial markets. An alternative approach is proposed where independent central banks coordinate their monetary policies through the adoption of common objectives and by building an appropriate institutional framework. When this coordination process has progressed to the point where interest rate developments are similar across the region, and if in the meantime the required institutional infrastructure has been build, the next step towards monetary unification can be taken among those central banks that so desire. The claim is that this transition path is likely to be robust and will limit the risk of currency crises.
Keywords: 330